Selection of Drought Tolerant Groundnut Genotypes (Arachis hypogaea L.) Based on Total Sugar and Free Amino acid Content (Journal of Environmental Science and Natural Resources, 2015)
For the selection of drought tolerant genotype, a field trial was conducted to monitor the quantitative changes of biochemical parameters such as total sugar and total free amino acid, due to water deficit condition in groundnut (Arachis hypogaea L.) seed. Plants were grown in irrigated and non-irrigated conditions. Mature seeds of forty genotypes and premature seeds of twenty one genotypes were freeze dried, defatted, ground and subjected to analysis. Drought exhibited no definite trend of increase or decrease for total free amino acid and sugar in mature as well as premature seed. Premature seed accumulated higher amount of total free amino acid having mean values 1.01% and 0.88% for control and drought respectively, than did the matured ones (control - 0.41% and drought - 0.43%). In mature seeds, drought augmented total free amino acid in twenty one genotypes and retrenched in the remaining nineteen. The data on immature seed was not much useful for selection purpose. In mature seeds of genotypes BINA-Chinabadam-2, 9267, ICGV-97228, ICGV-96295, and ICGV-95412, drought resulted in maximum elevation of total free amino acid. Accumulation of total sugar was higher in mature than in premature seeds. Drought brought about the increase in total sugar in mature seeds of thirty genotypes and decrease in the remaining ten. On imposing water stress, mature seeds of genotypes ICGV-92120, ICGV-94143, ICGV-96295, ICGV-95399 and ICGV-97228 showed comparatively high increment of total sugar. A particular genotype did not appear drought tolerant when the data on both the mature and premature seed are considered. However, in mature seed of genotype ICGV-97228, water stress induced a desired level of change in accumulation of total free amino acid and total sugar, and hence it may be preliminary considered as drought tolerant.DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22077 J. Environ. Sci. & Natural Resources, 6(2): 01-05 2013